A biomassa de macrófitas flutuantes como suplemento alimentar para o cultivo de organismos aquáticos: estratégia de manejo que favorece o rendimento econômico e ambiental na piscicultura - Proença, Maíra Alcântara (2015)
Macrophytes, in specific circumstances, may have accelerated growth to the point of becoming undesirable and harmful to the environmental balance. When this occurs, appropriate disposal methods are required, or preferably, the economic and environmentally friendly use of the macrophyte biomass. Thus, studies aiming to develop management strategies or to promote the use of macrophyte biomass as a source of energy to other aquatic organisms may contribute to the development of control techniques, or costeffective strategies to increment the development of aquaculture, decreasing production costs. The present research study aimed to test the use of macrophytes as a nutritional supplement to culture zooplankton with potential to be used as live food for juveniles of fishes and to test the inclusion of the biomass of two species of macrophytes Pistia stratiotes and Salvinia minima as an ingredient of fish rations. Analyses were carried out regarding the nutritional characteristics of the macrophytes and their dried biomass was crushed and added at increasing proportions to replace the algae, usedas a foof control. Experiments were carried out to measure individual and population growth rates and the reproductive performance of two species of Cladocera whose diet was supplemented with the weeds. The treatments with the inclusion of the macrophyte P. stratiotes as a food supplement for Daphnia laevis and Moina micrura resulted in similar or superior performance of that in the control, regarding individual and population growth rate, reproductive performance in the treatments where the algal biomass was replaced by 25% and 50% of P. stratiotes. Experiments were conducted with the tilapias where they were fed on diets formulated including percentages of 5, 10, 15 and 20% of the dry crushed biomass of the macrophytes. The greatest weight gain and individual growth was obtained with the diet with inclusion of 15% of the biomass of P. stratitotes, than the diet with 10% of S. minima resulting in lower production costs than that of the control diet. We suggest, therefore, the use of biomass in P.stratiotes with inclusion levels of 10% or 15% in the feed ration in order to ensure both economic and environmental benefits. The weeds that are often used to treat aquaculture effluents have great potential as a food supplement for zooplankton, and also as raw material for the production of fish feed. The use of this biomass is beneficial both as a management strategy of the fish pond and the economy fish cultures, resulting in both economic and environmental benefits